Implementasi Hypnoteaching dalam Pembelajaran Berdiferensiasi di Kabupaten Jeneponto - Ja'faruddin Ja'faruddin; Ayu Rahayu; Nur Wahidin Ashari (Jurusan Matematika FMIPA UNM, 2024)
The implementation of Hypnoteaching in differentiated learning at the Mathematics Teachers' Working Group (MGMP) in Jeneponto Regency aims to enhance mathematics teachers' professionalism through the integration of Hypnoteaching principles in differentiated learning. The program involves a series of systematic stages based on modern learning theories, including concept introduction, technique demonstration, guided practice, and comprehensive evaluation. Evaluation results show excellent achievement). Teacher competency transformation is evident through improved conceptual understanding and practical skills in applying Hypnoteaching. The program successfully established a community of practice for continuous professional development, with a sustainability interest rate of 3.93. These results demonstrate the effectiveness of the Hypnoteaching approach in improving the quality of differentiated mathematics learning in Jeneponto Regency.